Kadar Zat Gizi Makro, Serat, dan Sifat Organoleptik Biskuit Berbasis Tepung Ampas Kelapa (Cocos Nucifera L.) sebagai Makanan Alternatif Bagi Penderita Diabetes Melitus (DM) - Bella Septiviana; Lilia Faridatul Fauziah (Yayasan Literasi Sains Indonesia, 2024)
Blood sugar levels that are higher than normal, specifically when they are at least 200 mg/dL and fasting blood sugar levels are greater than or equal to 126 mg/dL, are indicative of diabetes mellitus, a chronic illness. Because patients frequently do not receive a diagnosis until their complications are known, diabetes mellitus is referred to as the silent killer. From the skin to the heart, DM can affect nearly every system in the body, potentially leading to issues. Biscuits are one substitute food that DM patients can be fed. The purpose of this study is to ascertain the nutritional value and acceptability of biscuits made with coconut dreg flour as a diabetic alternative. Both statistical analysis and an analysis of acceptability or organoleptic quality were employed in this study. The study's findings demonstrated that the nutritional value, color, flavor, texture, and aroma of biscuits made with coconut dreg flour were all significantly impacted. The P1 therapy biscuits offer the best care. The nutritional content and acceptability of the biscuits' color, flavor, scent, and texture are all impacted when coconut dreg flour is substituted.